Research on static mechanical properties of high-performance rubber concrete - Ge, Jinjin; Mubiana, Gilbert; Gao, Xiaoyu; Xiao, Yunfei; Du, Suyong (Frontiers in Materials, 2024)
High performance concrete (HPC) has the characteristics of high strength, high brittleness and low toughness, so it can not be widely used in engineering field. The rubber particles themselves have good elasticity and excellent wear resistance. To this end, rubber particles were used to prepare high performance rubber concrete (HPRC) instead of fine aggregate, and compressive strength and splitting tensile strength tests were carried out according to standard test methods. These data were evaluated, and it was found that adding different mesh number (10 mesh, 20 mesh, 30 mesh) and different content (10%, 20%, 30%) of rubber particles reduced the compressive and tensile properties of highperformance rubber concrete to different degrees. The rubber particles with l size of 30 mesh and content of 10% have the least influence on the mechanical properties of high-performance rubber concrete, and the compressive strength and tensile strength of HPC 28d only decrease by 18.19% and 5.56%, respectively. From the damage form, the addition of rubber particles makes the high performance concrete change from brittle to ductile. The research shows that recycling rubber from waste tires into concrete manufacturing is an environmentally friendly and feasible waste management strategy. These results have the potential to replace concrete in construction and promote sustainable growth.